PROBLEMATIKA TATA KELOLA KAWASAN EKONOMI KHUSUS GRESIK DI KECAMATAN MANYAR KABUPATEN GRESIK - Ahmad Aufa Kholqi; Supratiwi Supratiwi (Journal of Politic and Government Studies, 2026)
The acceleration of industrialization through the establishment of the Gresik Special Economic Zone (SEZ) in Manyar District has triggered the conversion of agricultural and fisheries land into industrial, residential, and commercial areas. This transformation has raised governance issues, particularly regarding the distribution of development benefits, environmental sustainability, and the protection of local communities’ rights. This study participation, aims to analyze the governance challenges of the Gresik SEZ using the Good Environmental Governance (GEG) theoretical framework, which encompasses the principles of the rule of law, access to information, transparency and accountability, decentralization, institutional capacity, and access to justice. The method employed is exploratory qualitative research through in-depth interviews, observations, and documentation involving local governments, technical agencies, and affected communities. The research findings indicate that the governance of the SEZ remains dominated by a top down approach, with fragmented inter-agency coordination and limited community participation. Land-use changes have led to the loss of community livelihoods, economic inequality, and the emergence of environmental issues that have not been adequately addressed. Additionally, access to justice tends to be pursued through informal mechanisms rather than formal legal channels. The study’s conclusions indicate that KEK governance has not fully reflected the principles of Good Environmental Governance, particularly regarding participation, transparency, and social-environmental justice. This research is limited to exploring issues within the 2021–2025 timeframe, so long-term dynamics have not yet been fully identified.